Using alice software with 4C-ID Model: effects in programming knowledge and logical reasoning - Costa, J. M.; Miranda, G. L. (Informatics in Education, 2019)
This paper presents an approach to the initial programming learning using the four components instructional model and the Alice software. The quasi-experimental design was developed with two groups of students that attended two schools with very different socioeconomic status and school retention levels. The differences obtained in the mean of the programming knowledge test when co-variated with the Logical Development Scale score were positive in the two groups, with no statistical significance in the difference between both (p = 0.05). The differences obtained in the Logical Development Scale score (Echelle Collective de Developpement Logique [ECDL]), before and after the experimental treatment, revealed positive differences in the experimental group with no statistical significance (p > 0.05), and in the control group with statistical significance (p < 0.05). These results suggest that the Alice software when combined with the 4C-ID instructional model has positive effects in programming learning and in logical reasoning.